(untitled) (Journal of Organizational Psychology, 2017)
Inconsistencies exist between how affect looks theoretically and how it has been tested. The purpose of this study is to empirically test the influence of various positive and negative trait affect combinations on employee attitudes, intentions, and behaviors. Additionally, this study examines the differential influence of the source of the affect (from a peer vs. from a leader). A laboratory experiment was utilized in order to test the hypotheses. Results show that a combination of high positive affect and low negative affect for both the leader and the peer is associated with the highest outcomes